Pulse Duration Dependent Asymmetry in Molecular Transmembrane Transport Due to Electroporation in H9c2 Rat Cardiac Myoblast Cells In Vitro - Tina Batista Napotnik (MDPI AG, 2021)
Electroporation (EP) is one of the successful physical methods for intracellular drug delivery, which temporarily permeabilizes plasma membrane by exposing cells to electric pulses. Orientation of cells in electric field is important for electroporation and, consequently, for transport of molecules through permeabilized plasma membrane. Uptake of molecules after electroporation are the greatest at poles of cells facing electrodes and is often asymmetrical. However, asymmetry reported was inconsistent and inconclusive—in different reports it was either preferentially anodal or cathodal. We investigated the asymmetry of polar uptake of calcium ions after electroporation with electric pulses of different durations, as the orientation of elongated cells affects electroporation to a different extent when using electric pulses of different durations in the range of 100 ns to 100 µs. The results show that with 1, 10, and 100 µs pulses, the uptake of calcium ions is greater at the pole closer to the cathode than at the pole closer to the anode. With shorter 100 ns pulses, the asymmetry is not observed. A different extent of electroporation at different parts of elongated cells, such as muscle or cardiac cells, may have an impact on electroporation-based treatments such as drug delivery, pulse-field ablation, and gene electrotransfection.